2011
DOI: 10.1293/tox.24.143
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Alterations of Lysophosphatidic Acid Receptor Genes in Rodent Tumors by Experimental Models

Abstract: Lysophosphatidic acid (LPA) is a bioactive mediator and induces several biological effects, including cell proliferation, migration, morphogenesis and differentiation. LPA interacts with at least six G protein-coupled receptors (GPCRs), including LPA receptor-1 (LPA1), LPA2, LPA3, LPA4, LPA5 and LPA6. These receptors show different biological functions through the binding of LPA, dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Aberrant LPAR5 mRNA expression due to DNA methylation in RLCNR and RH777 lung cancer cells was seen to contribute toward enhanced proliferation [132]. This group also reported that overexpression of LPAR3 attenuated migration in the same cells [133].…”
Section: Lung Cancermentioning
confidence: 90%
“…Aberrant LPAR5 mRNA expression due to DNA methylation in RLCNR and RH777 lung cancer cells was seen to contribute toward enhanced proliferation [132]. This group also reported that overexpression of LPAR3 attenuated migration in the same cells [133].…”
Section: Lung Cancermentioning
confidence: 90%